Dancing on a tightrope: The reputation management of local governments in response to public protests in China. (21st October 2020) - Wei, Yuming; Guo, Yue; Su, Jun
Abstract: The purpose of this study is to explore the characteristics of local government's reputation management in response to public protests under the dual pressure from higher‐level authorities and the public. This study connects reputation management theory to the literature on local governments in the dual pressure dilemma. By comparing three cases of how local governments respond to public protests against nuclear facilities in China, we conclude that different pressures perceived by local governments generate diverse behaviours of reputation management in response to public protests. If the perceived bottom‐up pressure is higher, local governments will focus on their moral reputation and make concessions to the public; if the perceived top‐down pressure is higher, local governments will build a performative reputation to meet the demands of higher‐level authorities and suppress public protests; if local governments face dual high pressures, they will comply with all normative procedures and avoid accountability to any party.